Tecnología y enseñanza de las matemáticas: desarrollo y aportes de la aproximación instrumental - Artigue, Michèle (2011)
What do we consider now from the teaching of mathematics? What we consider as progress, regression or a failure? These questions are key issues in Mathematics Education.We cannot answer these questions without taking into account the technological factor. This in part prompted the choice of topic for my contribution to this conference. The other reason is that I have been working in that area for more than twenty years dealing with these questions, whether as a teacher or as a researcher and I would like to share with you the thoughts that inspired me this experience.